30-Second Medicine: The 50 crucial milestones, treatments and technologies in the history of health, each explained in half a minute - Gabrielle M. Finn (Ivy Press, 2017)
What does the Hippocratic oath actually say? Who originally discovered antibiotics? And when were hospitals invented? Find out the answers to these questions and many others in '30-Second Medicine'. Taking the story from the first 'medicines' direct from nature to today's keyhole surgery, and with a look toward future developments, it's an engrossing journey.